(3CfhGQ GdJfRjd hCSQGQ GdJChjds - (3YHO Gddg Hf YeQ Hf eMeO Hf Ydj , GdTjQGRj GdHjVGhj, CHh SYjO CHh GdNjQ fGUQ GdOjf,J (B685 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi GfRd GdaQbGf s
(3BNQgG (B:s
(3hGUd GdbVGA GdaUd HJeGe GdGeQ hCUd GdMce s
(3GdfSNI HgG MhGTs
(3Jedc CMeO Hf GSeGYjd Hf eMeO JjehQs
(3ecJhHI HQSe Gdedc GdXGgQ s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs